Qualification by HHF tests of W coatings on Inconel superalloy for COMPASS-U plasma-facing components - Renaud Dejarnac; Jiří Matějíček; Henri Greuner; Bernd Böswirth; J. Gerardin; Jaromír Kopeček; Daniil Kirhetov (Nuclear Materials and Energy)
Coating Inconel tiles by tungsten is a necessary step towards the full tungsten first wall coverage of the COMPASS-U tokamak. Thin tungsten coatings on Inconel based on physical vapor deposition were successfully produced consequently to a programme of R&D within the COMPASS Upgrade project by three different suppliers. This contribution presents the qualification phase of these tungsten coatings under COMPASS-U relevant high heat fluxes (50 cycles at 10  MW/m2, 100 cycles at 30  MW/m2) in the neutral beam test facility GLADIS. The behavior of the different tungsten coatings during exposures and the main conclusions from the post-mortem analysis are presented. The most important result is that under COMPASS-U relevant heat fluxes, no damage was observed on the front face of all samples, proving the practicability of such coatings for fusion application.